Investigating the coorelationship between level of self-efficacy and gender - Sawari, Siti Salwa; Kazeem, Bakare; Mansor, Norwati (Contemporary Research Center Australia, 2013)
as people’s belief about their capabilities to produce designated level of performance that exercise influences over events that affect their lives (Bandura 1977). Self-efficacy plays a vital role in students’ lives and future. The reduction and improvement of self-efficacy will contribute towards their achievement in life. This present study was designed to investigate three main objectives. First, it examines the level of self-efficacy among secondary students. Second, it explores whether there is a statistically significant difference in the level of self-efficacy between male and female school students. Third, is they any correlationship between self-efficacy and gender. A total of 122 students sampled from two school in Muar participated in the survey, employing a 22-item questionnaire measuring General Self-efficacy (GSE) and Fertment Self-efficacy Scale. The items were pilot-tested before being administered to the respondents. The data was analyzed quantitatively using descriptive statistics, independent-samples t-tests and Pearson’s product-moment correlation tests. The result showed that the majority of students experience a moderate level of self-efficacy. Regarding the comparison level of self-efficacy between male and female, the findings of the current study shows that, there are significant differences for both gender. In additions, with regards to the correlations between selfefficacy and gender, the study revealed that there are positive correletionship.